AntiV‐SGN: a universal antiviral strategy to combat both RNA and DNA viruses by destroying their nucleic acids without sequence limitation. Issue 9 (25th May 2022) - Tian, Kun; Qi, Zhen; Chi, Ying; Qiang, Huanran; Wang, Pei; Liu, Yu; Zhou, Guohua; Zhu, Fengcai; Guo, Qinglong; Xu, Shu
Summary: Numerous viral outbreaks have threatened us throughout history. Here, we demonstrated a nucleic acid‐based antiviral strategy named AntiV‐SGN. Unlike those CRISPR‐mediated methods, AntiV‐SGN has advantages of no targets' sequence limitation, such as protospacer adjacent motif (PAM) or protospacer flanking sequence (PFS), being universal for both DNA and RNA viruses. AntiV‐SGN was composed of a FEN1 protein and specific hpDNAs targeting viruses' nucleic acid. Its antiviral ability was tested on SARS‐CoV‐2 and HBV respectively. Reporter assays in human cells first illustrated the feasibility of AntiV‐SGN. Then, it was verified that AntiV‐SGN destroyed about 50% of live RNAs of SARS‐CoV‐2 in Vero cells and 90% cccDNA of HBV in HepG2.2.15 cells. It was also able to remove viral DNA integrated into the host's genome. In the mouse model, AntiV‐SGN can be used to significantly reduce HBV expression at a level of 90%. Actually, in some cases, when viruses mutate to eliminate PAM/PFS or hosts were infected by both DNA and RNA viruses, AntiV‐SGN could be a choice. Collectively, this study provided a proof‐of‐concept antiviral strategy of AntiV‐SGN, which has potential clinical value for targeting a wide variety of human pathogens, both known and newly identified. Abstract : Here we demonstrated a nucleic‐acid‐based antiviral strategy named AntiV‐SGN.We demonstrated the ability to cleave vRNA, cccDNA, integrated vDNA, and other viral gene expression and replication parameters by the AntiV‐SGN strategy. In summary, this study provided a proof‐of‐concept antiviral strategy of AntiV‐SGN to combat both DNA and RNA virus, which has potential clinical value for targeting a wide variety of human pathogens, both known and newly identified.